Chronic lithium treatment alters NMDA and AMPA receptor synaptic availability and dendritic spine organization in the rat hippocampus - Caffino, Lucia; Targa, Giorgia; Mallien, Anne Stephanie; Mottarlini, Francesca; Rizzi, Beatrice; Homberg, Judith R.; Gass, Peter; Fumagalli, Fabio (Current neuropharmacology, 2024)
Background: The mechanisms underlying the action of lithium (LiCl) in bipolar disorder - (BD) are still far from being completely understood. Previous evidence has revealed that BD is characterized - by glutamate hyperexcitability, suggesting that LiCl may act, at least partially, by toning down - glutamatergic signaling abnormalities. - - - Objective: In this study, taking advantage of western blot and confocal microscopy, we used a combination - of integrative molecular and morphological approaches in rats exposed to repeated administration - of LiCl at a therapeutic dose (between 0.6 and 1.2 mmol/l) and sacrificed at two different time - points, i.e., 24 hours and 7 days after the last exposure. - - - Results: We report that repeated LiCl treatment activates multiple, parallel, but also converging forms - of compensatory neuroplasticity related to glutamatergic signaling. More specifically, LiCl promoted a - wave of neuroplasticity in the hippocampus, involving the synaptic recruitment of GluN2A-containing - NMDA receptors, GluA1-containing AMPA receptors, and the neurotrophin BDNF that are indicative - of a more plastic spine. The latter is evidenced by morphological analyses showing changes in dendritic - spine morphology, such as increased length and head diameter of such spines. These changes may - counteract the potentially negative extra-synaptic movements of GluN2B-containing NMDA receptors - as well as the increase in the formation of GluA2-lacking Ca2+-permeable AMPA receptors. - - - Conclusion: Our findings highlight a previously unknown cohesive picture of the glutamatergic implications - of LiCl action that persist long after the end of its administration, revealing for the first time - a profound and persistent reorganization of the glutamatergic postsynaptic density receptor composition - and structure.
Online veröffentlicht: 15 September 2023
Gesehen am 21.10.2024